Encountering Rural Transformation: A Catalyst for Exchanging Narratives of Place?. Issue 1 (2nd January 2017) - Krag, Mo Michelsen Stochholm
Abstract: While the major cities in Denmark experience population growth, the villages in surrounding rural areas face abandonment and decay. European Union and state funds are used for the demolition of abandoned houses and the rapid eradication of cultural values under the guise of state-authorized clean-up projects. This paper outlines an attempt to establish a counter-practice of radical preservation based on a series of transformations of abandoned buildings in various rural villages. The main focus is on one particular transformation, "The controlled ruin at the church, " as it explored the responses of the local community throughout the entire period since the start of the project in March 2014. The aim of this transformation was to reveal and preserve material and immaterial values endangered by the forthcoming demolition such as aspects of cultural heritage, local narratives, and building density. The presence of "The controlled ruin at the church" in the rural village catalyzed an exchange of memories of the place among the local inhabitants. Furthermore, the subsequent decay process showed a positive influence on the local attitude towards the implemented strategy. Bringing in surveyed examples of a ruinous village on the Italian island of Sicily, a depleted extraction plant in Germany and the sudden depopulation of the US city of Detroit, Michigan, the emerging counter-practice is contextualized to international efforts in the field and precedents of revitalized ruins.